simplificati va rog urgent dau coroană
![Simplificati Va Rog Urgent Dau Coroană class=](https://ro-static.z-dn.net/files/db5/55cb1b3c0fbcb544652b5b4f340689d5.jpg)
[tex]\frac{3x^{2}-12xy+12y^{2} }{x^{2}-4y^{2} } =\\\frac{3(x^{2}-4xy+4y^{2}) }{(x-2y)(x+2y)} =\\\frac{3(x-2y)^{2} }{(x-2y)(x+2y)} =\\\frac{3(x-2y)}{x+2y} =\\\frac{3x-6y}{x+2y}[/tex]
Răspuns:
3(x - 2y)/(x + 2y)
Explicație pas cu pas:
(3x² - 12xy + 12y²)/(x² - 4y²) =
= 3(x² - 4xy + 4y²)/(x -2y)(x + 2y)
= 3(x - 2y)²/(x -2y)(x + 2y)
= 3(x - 2y)/(x + 2y)